2016
DOI: 10.1111/1750-3841.13426
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profiles, Antioxidant Activities, and Neuroprotective Properties of Mulberry (Morus atropurpurea Roxb.) Fruit Extracts from Different Ripening Stages

Abstract: The present work investigated the phenolic profiles (including nonanthocyanin and anthocyanin phenolics), antioxidant activities, and neuroprotective potential of mulberry fruit (MF) (Morus atropurpurea Roxb.) grown in China at different ripening stages. High-performance liquid chromatography-tandem mass spectrometry method (HPLC-MS/MS) was used to identify and quantify the phenolic compounds. The antioxidant capacity, total phenolic content (TPC), total flavonoid content (TFC), and total monomeric anthocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…Mulberry fruit has antioxidative properties, mainly due to the presence of polyphenols. 9 In particular, anthocyanins in mulberry fruit have been shown to inhibit the oxidation of free radicals. 10 The freeze-dried mulberry fruit powder improved antioxidant status of blood and hepatic superoxide dismutase and glutathione peroxi-dase activity in rats fed high-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry fruit has antioxidative properties, mainly due to the presence of polyphenols. 9 In particular, anthocyanins in mulberry fruit have been shown to inhibit the oxidation of free radicals. 10 The freeze-dried mulberry fruit powder improved antioxidant status of blood and hepatic superoxide dismutase and glutathione peroxi-dase activity in rats fed high-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…At present, isolation and characterization of the phytochemicals from mulberry fruits are imperative, as these fruits are consumed in many countries for dietary enhancement (10). Mulberry fruits harbor a diverse array of biological elements that have elite nutritional value and, many of them decorated with antioxidant properties due to the presence of polyphenolic groups (16).…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…In previous studies, Yang et al [9] investigated mulberry fruit at different stages of ripeness, and found that fully ripened mulberry fruit extracts contained the highest TPC. Here, the mulberry fruits tested were all mature, allowing meaningful comparisons of TPC levels among different mulberry cultivars.…”
Section: Tpc and Antioxidant Properties As Assessed By Frap Abts Anmentioning
confidence: 99%
“…takes only 25 to 30 d, which is relatively short compared with other fruits. [9] Mulberry fruits are increasingly popular with consumers because of their unique flavor, and nutritional and medicinal values. [10] Mulberry fruits are eaten in various forms, including fresh, or processed into jams and juices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation